Causal relationships exist between polycystic ovary syndrome and adverse pregnancy and perinatal outcomes: a Mendelian randomization study - Ma, Yuanlin; Cai, Jiahao; Liu, Lok-Wan; Wen, Tianrui; Huang, Weina; Hou, Wenhui; Wei, Zixin; Xu, Yan; Xu, Yanwen; Wang, Yizi; Mai, Qingyun (Frontiers in Endocrinology, 2024)
Introduction Previous observational studies have shown that polycystic ovary syndrome (PCOS) was associated with adverse pregnancy and perinatal outcomes. However, it remains controversial whether PCOS is an essential risk factor for these adverse pregnancy and perinatal outcomes. We aimed to use instrumental variables in a two-sample Mendelian randomization (MR) study to determine causality between PCOS and adverse pregnancy and perinatal outcomes. Materials and methods Summary statistics were extracted from a recent genome-wide association study (GWAS) meta-analysis conducted in PCOS, which included 10,074 cases and 103,164 controls of European ancestry. Data on Adverse pregnancy and perinatal outcomes were summarized from the FinnGen database of European ancestry, which included more than 180,000 samples. The inverse variance weighted (IVW) method of MR was applied for the main outcome. To assess heterogeneity and pleiotropy, we conducted sensitivity analyses, including leave-one-out analysis, weighted median, MR-PRESSO (Mendelian Randomization Pleiotropy RESidual Sum and Outlier), and MR-Egger regression. Results Two-sample MR analysis with the IVW method suggested that PCOS exerted causal effects on the risk of hypertensive disorders of pregnancy [odds ratio (OR) 1.170, 95% confidence interval (CI) 1.051–1.302, p = 0.004], in particular gestational hypertension (OR 1.083, 95% CI 1.007–1.164, p = 0.031), but not other pregnancy and perinatal diseases (all p > 0.05). Sensitivity analyses demonstrated pleiotropy only in pre-eclampsia or eclampsia (p = 0.0004), but not in other pregnancy and perinatal diseases (all p > 0.05). The results remained consistent after excluding two outliers (all p > 0.05). Conclusions We confirmed a causal relationship between PCOS and hypertensive disorders of pregnancy, in particular gestational hypertension, but no association with any other adverse pregnancy or perinatal outcome. Therefore, we suggest that women with PCOS who are pregnant should have their blood pressure closely monitored.